Clonality drives structural patterns and shapes the community assemblage of the Mediterranean Fagus sylvatica subalpine belt - Saulino, Luigi; Rita, Angelo; Allegrezza, Marina; Zotti, Maurizio; Mogavero, Valentina; Tesei, Giulio; Montecchiari, Silvia; Allevato, Emilia; Borghetti, Marco; Bonanomi, Giuliano; Saracino, Antonio (Frontiers in Plant Science, 2022)
Past anthropogenic disturbances lowered the altitudinal distribution of the Mediterranean Fagus sylvatica forests below 2,000 m a.s.l.. Accordingly, our current understanding of the southern distribution range of F. sylvatica forests is restricted to managed stands below this elevation, neglecting relic forests growing above. This study sheds light on the structure and species assemblage of an unmanaged relict subalpine F. sylvatica stand growing within the core of its southernmost glacial refugia and at its highest species range elevation limit (2,140 m a.s.l.) in Southern Apennines (Italy). Here, tree biometric attributes and understory species abundances were assessed in eight permanent plots systematically positioned from 1,650 to 2,130 m a.s.l.. In the subalpine belt, F. sylvatica formed a dense clonal stem population that was layered downward on the steepest slopes. The density and spatial aggregation of the stems increased, while their stature and crown size decreased. Above 2,000 m, changes in tree growth patterns, from upright single-stemmed to procumbent multi-stemmed, and canopy layer architecture, with crowns packed and closer to the floor, allowed for the persistence of understory herbaceous species of biogeographic interest. Clonal layering represents an adaptive regeneration strategy for the subalpine belt environmental constraints not previously recognised in managed Mediterranean F. sylvatica forests. The clonal structure and unique species assemblage of this relic forest highlight the value of its inclusion in the priority areas networks, representing a long-term management strategy of an emblematic glacial and microclimatic refugia.